Una Reflexión crítica acerca del paradigma del “Buen Vivir” como alternativa al modelo de desarrollo. - Marqués, Tania (2020)
Buen Vivir, a set of ideas, knowledge and practices, constitutes an alternative to the development model in Latin America. This article presents a critical reflection on this paradigm, especially based on contributions from Silvia Rivera Cusicanqui and Lorena Cabnal, and on notions from experiences of Latin American feminisms.